The impact of mediated party issue strategies on electoral support. (November 2017) - Bos, Linda; Lefevere, Jonas M; Thijssen, Roos; Sheets, Penelope
Based on agenda-setting, priming and issue ownership theory, we know that issue ownership and party visibility in the news can be used as strategies to affect electoral support. Thus far, it is, however, unclear whether these effects are independent or work interactively. This study aims to fill this gap. We focus on the Partij voor de Vrijheid, the prominent Dutch right-wing populist party, and draw upon an experimental design in which we exposed a sample of Dutch voters ( N = 600) to media coverage on one of four issues – an owned issue, an unowned issue, an issue owned by another party and a contested issue – featuring either a party cue or not. The results indicate that the impact of issue coverage is moderated by party cues: attention to owned issues and unowned issues increases support only when party cues are present. Attention to contested and trespassing issues does not increase support.